Common Types and Methods of Drug Usage In Iran: A Systematic Review and Meta-Analysis - Hamid Taghinejad1, Ali Khorshidi2, Noorollah Yadeghari3, Walieh Menati4, Rostam Menati5, Aziz Kassan (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction: Drug usage is a prevalent social and health problem in most countries. The highest prevalence of drug abuse has been reported among people aged 30-40 years old. The purpose of this study was to determination of the types of drugs and the methods of drug usage in Iran in a systematic and meta-analysis study.Methods: This study was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Databases ofSID, Iran Doc, ISI, Cochrane library, Science direct, PubMed/Medline, and Scopus were independently searched by two researchers using MeSH keywords. Articles published between 2004 and 2018 were recruited.Data was analyzed using random effectsmodel using STATA-SE12 software. Heterogeneity among studies was investigated using, T2 and I2statistical indices.Results: Initial search retrieved 90 articles from which 7 articles with desirable quality were finally analyzed. Opium was the most common in used narcotic50 %(95% CI: 35-66%) followed by opium extract44%(95% CI: 5-83%), and heroin 19%(95% CI: 12-26%). Using more than one narcotic was observed in 9% (95% CI: 4-15%). The inhalation was the most common method of usage72 %( 95% CI: 61-83%) followed by oral consumption 32%(95% CI: 9-54%) and injection 14%( 95% CI: 05-24%).Conclusion: Drug abuseis a common phenomenon in Iran. It is amenable to reduce the tendency to using drugs by providing appropriate training, informing the risks of drug abuse, and identifying and educating high-risk groups.